Hygroelectric Energy Harvesting by Daily Humidity Cycles and its Thermodynamics - Yusuke Komazaki; Taiki Nobeshima; Hirotada Hirama; Yuichi Watanabe; Kouji Suemori; Sei Uemura (Advanced Energy & Sustainability Research)
Atmospheric moisture is emerging as a ubiquitous energy source for energy harvesting. However, a practical long‐life device has not been realized, and theoretical aspects including mechanisms and thermodynamics have not been fully clarified. Here, this study provides a practical device and a thermodynamic theory for a concentration cell‐based hygroelectric generator (hygroelectric cell, HEC), which enables high‐power and long‐term electricity generation by day/night humidity changes. Using a Li1+x+yAlxTi2−xSiyP3−yO12 glass–ceramic solid electrolyte membrane with no water permeability, an ideal HEC without self‐discharge is realized. The ideal HEC generates electricity in an outdoor environment for over three months with a maximum power density of 60.4 μW cm−2 and an average power density of 3.0 μW cm−2. The maximum power density in the experimental environment reaches 436 μW cm−2. This is 68 times higher than conventional HECs with polymer‐based cation‐exchange membranes. The ideal HEC can also drive a wireless sensor for more than four months. Furthermore, a thermodynamic model of the ideal HEC, which enables calculations of the maximum work and maximum efficiency, is derived and the model is verified by experiments. This study provides new insights into both thermodynamic theory and device development aspects of the humidity‐based energy harvesting.